Circadian Rhythm Sleep-Wake Disorders. Issue 4 (August 2020) - Zee, Phyllis C.; Abbott, Sabra M.
ABSTRACT: PURPOSE OF REVIEW: This article provides an overview of circadian physiology and discusses common presentations and treatment strategies for the circadian rhythm sleep-wake disorders. RECENT FINDINGS: Circadian rhythms are present throughout the body, and appreciation for the role that circadian dysregulation plays in overall health is increasing, with mounting associations between circadian disruption and cardiometabolic disease risk. SUMMARY: It is important to recognize the ubiquitous role that circadian rhythms play throughout the brain and body. An understanding of circadian neurophysiology will provide insight into the means by which patients with a variety of neuropathologies at the level of the retina, optic nerve, or hypothalamus may also be at risk for circadian dysfunction.